A study of the relationship between cytokine levels and the response to anti-VEGF therapy in polypoid choroidal vasculopathy with different choroidal thicknesses - Dong, Su; Fan, Pan; Yu, Haotian; Jiang, Bo; Sun, Dawei (Frontiers in Endocrinology, 2024)
Polypoidal choroidal vasculopathy (PCV) is an irreversible retinal choroidal disease. Individuals with PCV exhibit diverse baseline characteristics, including systemic characteristics, ocular traits, metabolic factor levels, and different responses to intravitreal anti-VEGF therapy. This study aims to investigate the pathogenesis of PCV by analyzing the systemic characteristics, ocular traits, and cytokine levels at baseline within a cohort of patients who exhibit different responses to anti-VEGF treatment. This is a provisional file, not the final typeset article markedly lower observed in the optimal anti-VEGF response group, while TNF-α showed the opposite trend. Logistic regression analysis indicated that VEGF, VCAM-1, and TNF-α in the aqueous humor were independent risk factors for a suboptimal anti-VEGF response. After adjusting other risk factors, the risk of suboptimal anti-VEGF response decreased to 0.998-fold, 0.997-fold, and 1.294-fold. The AUC values for VEGF, VCAM-1, and TNF-α were determined to be 0.805, 0.846, and 0.897, respectively. Furthermore, the risk of VEGF, VCAM-1, and TNF-α were significantly associated with an increased risk of suboptimal anti-VEGF response after correction for risk factors in the thick choroid group.Our study demonstrated that PCV exhibits systemic and ocular characteristics variations based on different anti-VEGF responses. The levels of cytokines in aqueous humor were found to have a significant correlation with the anti-VEGF response in PCV. VEGF, VCAM-1, and TNF-α are potential targets for assessing treatment response in thick choroidal PCV.